PANEL COINTEGRATION ANALYSIS OF CONSUMER CONFEDENCE AND PERSONAL CONSUMPTION IN THE EUROPEAN UNION - ÇELİK, SADULLAH (VILNIUS GEDIMINAS TECH UNIV, 2009)
This study examines the relationship between consumer confidence, personal consumption, and other relevant economic and financial variables for 9 European Union countries. It is argued that consumer confidence is an early indicator of future rates of growth in an economy through the consumption channel. Therefore, an increase in consumer confidence should translate into higher rates of consumption in the future, leading to a possible rise in economic growth. Our panel data analysis, conducting panel unit root tests and panel cointegration tests, tries to measure the effects of changes in consumer sentiment on personal consumption expenditures while accounting for other significant economic and financial variables such as stock exchange index, real exchange rates and interest rates. The empirical findings show the existence of a long-run relationship. Thus, consumers are able to detect early signals about future rates of economic growth as they contribute through the consumption channel.
Keywords: consumer confidence; personal consumption; panel cointegration; ROOT TESTS; CONFIDENCE; EXPECTATIONS; HYPOTHESIS; VECTORS; INCOME